Kewirausahaan Sosial Dalam Pemberdayaan Masyarakat - Rizki Saputra, Bima (JAMBIS : Jurnal Administrasi Bisnis, 2024)
Community empowerment aims to improve community empowerment for the better, especially in the social, economic, and political fields. Meanwhile, social entrepreneurship is a concept that prioritizes collaboration, innovation, and creation in its implementation to produce economic activity. Based on this, there is great hope that social entrepreneurship can be a solution for community empowerment to solve social problems that exist in society, namely poverty. Thus, social entrepreneurship plays a role in community empowerment which aims to improve community welfare. The purpose of writing this literature study is to find out and prove that social entrepreneurship plays a role in community empowerment. This writing was compiled using the literature study method and continued by concluding the concepts that were the focus of the discussion, conducting a search on previous research related to community empowerment and the role of social entrepreneurship. In this article, the results show that social .Entrepreneurship activities have their own role in community empowerment. That way, entrepreneurship can be considered to play an important role in community empowerment which aims to improve people’s welfare